Clinical course features of newly diagnosed pulmonary tuberculosis treatment failure - Yasinskyi, R. M.; Kovalenko, O. O.; Smirnova, V. V.; Krasnevich, A. M. (Zaporozhye Medical Journal, 2016)
Percentage of patients with newly diagnosed tuberculosis treatment failure is 22,6 % in the world and is approximately 12 % according to the official statistics in Zaporizhzhia. Aim. To establish anamnestic, clinical-radiographic and laboratory features of the tuberculosis course in patients with newly diagnosed tuberculosis treatment failure. Materials and methods. A retrospective analysis of 88 patient`s histories who were treated at the Zaporizhzhia Regional Clinical Tuberculosis Dispensary in 2013-2015 years was carried out. Patients were divided into 2 groups: 49 patients with treatment failure (TF) have been included into 1st group, 39 people who successfully completed the course of therapy (NDTB) were in the 2nd group. Results. It was found that 63,3 % of TF patients carried fluorography untimely and 26,6 % have not been inspected more than 5 years, p˂0,05. Infiltrative (55,1 %) and disseminative (34,7 %) tuberculosis clinical forms in TF patients prevailed in the structure of the lung lesions. Approximately 90 % of TF patients had lung lesion volume more than one lobe or both of the lungs (p˂0,001) with the presence of several or multiple destructions in 79 % of patients with a size greater than 3 cm in 56 % of patients compared with the fact, that 46 % of patients with NDTB limited tuberculosis diagnosed with single or several destructions with sizes up to 3 cm in 86 % cases, p˂0,05. When TF percentage of patients with massive bacterial excretion prevailed, p˂0,05. In the presence of drug resistance in 70 % polyresistance determined, whereas 26 % of NDTB bacterial excretion was determined only by culture methods and in resistance cases it was monoresistance in 67% patients. Terms of bacteriological conversion at TF were 6,3 ± 0,2 months and greater than 6 months in 30,6 % of patients. Destruction not healed in 85,4 % of patients, but in most cases, their sizes did not exceed 2 cm at the end of treatment. Long terms of bacteriological conversion and destructions healing in TF patients demonstrate the necessity for long-term etiotropic therapy in patients with smear-massive bacterial excretion and disseminative destructive tuberculosis. The low proportion of destructions healing in these patients determines searchings’ for ways to the timely surgical and complex pathogenetic treatment.